2020
DOI: 10.1183/20734735.0328-2019
|View full text |Cite
|
Sign up to set email alerts
|

Nebuliser hygiene in cystic fibrosis: evidence-based recommendations

Abstract: Nebulised therapies are extensively used in the daily therapeutic management of cystic fibrosis both for mucociliary clearance and for the management of chronic infections. Extensive developments have been made in relation to nebulised drug delivery mechanisms and drug formulations, and guidelines have been prepared that have addressed the appropriate use of such therapies. However, due to these developments, a plethora of nebuliser devices and drug chambers exist, and frequently, the limited guidance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 74 publications
0
9
0
Order By: Relevance
“…27,28 These studies emphasize that while drying is a very important step, it is not enough for absolute elimination of NTM and S. aureus. 22 In our study, 48% of participants were using inappropriate places for nebulizer storage, which decreased to 12.1% following training.…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…27,28 These studies emphasize that while drying is a very important step, it is not enough for absolute elimination of NTM and S. aureus. 22 In our study, 48% of participants were using inappropriate places for nebulizer storage, which decreased to 12.1% following training.…”
Section: Discussionmentioning
confidence: 46%
“…Since it is a cheap, user friendly and accessible method has been more commonly used in recent years. 22,23 Although relatively high percentage of patients reported doing both cleaning and disinfection; only a few participants have been following entire process according IPC guidelines before the education. It is also important to emphasize that self-reported care of nebulizers does not necessarily translate into daily practice.…”
Section: Discussionmentioning
confidence: 99%
“…CF nebulizer devices have also been shown to be a source of respiratory pathogens 10 and guidelines have been published which address nebulizer cleaning and disinfection, to ensure that such devices are not the origin of respiratory infection/reinfection 11,12 . In regulatory terms, manual toothbrushes (Regulation Number 872.6855) are considered class 1 devices by the Food and Drug Administration, with low to moderate risk, accompanied with General Controls (https://www.fda.gov/medical-devices/overview-device-regulation/regulatory-controls), whereas nebulizers (Regulation Number 868.5630) are considered class 2 devices, accompanied with General Controls and Special Controls (https://www.fda.gov/medical-devices/overview-device-regulation/classify-your-medical-device)…”
Section: Introductionmentioning
confidence: 99%
“…8,9 CF nebulizer devices have also been shown to be a source of respiratory pathogens 10 and guidelines have been published which address nebulizer cleaning and disinfection, to ensure that such devices are not the origin of respiratory infection/reinfection. 11,12 Table 1 describes the microbial isolates (n = 80; Gram positive= 33;…”
mentioning
confidence: 99%
“…There is often confusion on what is the best way to clean and disinfect a nebulizer, an issue that adds extra burden to patients and their families [ 3 , 10 , 11 ]. It has been reported that manufacturers’ instructions are not always consistent with guidelines for CF patients and that patients receive conflicting information from different sources [ 6 , 12 , 13 , 14 ]. This evidence underlines the importance of healthcare providers reviewing instructions with CF patients and their families.…”
Section: Introductionmentioning
confidence: 99%